Understanding London's summertime cloud cover. (1st December 2021) - Theeuwes, Natalie E.; Boutle, Ian A.; Clark, Peter A.; Grimmond, Sue
Abstract: Cities are a source of complex land–atmosphere interactions. Spatial differences in the energy balance and enhanced surface roughness interact with the atmosphere to alter clouds and precipitation. Here, we explore how London (UK) alters cloud formation during the spring and summer. The Met Office's high‐resolution operational forecasts predict enhanced cloud cover over the city, as found in observations, but underpredicts the intensity. During low wind speeds, cloud enhancement over the city is strongest and linked to an urban‐induced thermal circulation. These circulations advect moist air from the city edge inwards, transporting it upwards with a large moisture convergence over the urban area. At around 1, 000 m above the surface, the turbulent moisture flux takes over the moisture transport to the cloud layer. A relative humidity budget shows the moisture flux in the upper boundary layer to be the largest contribution to the urban–rural differences in relative humidity. Abstract : This study explores how London (UK) alters cloud formation during the spring and summer. The Met Office's high‐resolution operational forecasts predict enhanced cloud cover over the city, as found in observations, but underpredicts the intensity. During low wind speeds, cloud enhancement over the city is strongest and linked to urban‐induced thermal circulation. These circulations advect moist air from the city edge inwards, transporting it upwards with a large moisture convergence over the urban area.